OP0201 Exomewide Association Study of Ankylosing Spondylitis Identifies Additional Coding Region Genetic Associations with as and Strengthens Evidence of Shared Genetic Background with Inflammatory Bowel Disease. (9th June 2015) - Robinson, P.C.; Leo, P.; Pointon, J.J.; Harris, J.; Cremin, K.; Bradbury, L.A.; Stebbings, S.; Harrison, A.; Duncan, E.; Wordsworth, P.; Brown, M.A.
Abstract : Background: Ankylosing spondylitis is a common chronic immune-mediated arthropathy affecting primarily joints of the spine and pelvis. The condition is strongly associated with HLA-B27, and association with other HLA variants has been demonstrated. In addition to these effects, to date 30 non-MHC loci have been associated with the disease, and significant additional heritability remains. Objectives: To identify further genetic variants associated with ankylosing spondylitis. Methods: We undertook a study of ankylosing spondylitis using 5, 040 patients and 21, 133 healthy controls using the Illumina Exomechip microarray. This assays all coding variation in the genome along with genomewide association hits and major histocompatibility tag single nucleotide polymorphisms. Analysis was carried out with logistic regression using principal component analysis to correct for any population stratification. Results: Novel associations achieving genomewide significance were found in USP8 ( P =3.5 x 10 -52, OR =1.97) and CDKAL1 ( P =1.8 x10 -8, OR =1.18). Suggestive associations with common variants in FAM118A ( P =5.9 x 10 -8, OR =1.16), C7orf72 ( P =1.9 x 10 -7, OR =1.14) and FAM114A1 ( P =1.4 x 10 -6, OR =1.14) were also found. A low frequency association (MAF cases/controls: 0.0044/0.0017) was found in patatin-like phospholipase domain containing 1 ( PNPLA1) at a suggestive level of significance ( P =1.5 x 10 -6, OR =2.6). Conclusions: This study describes novel genetic associations with ankylosing spondylitis. Three of the variants have been previously associated with inflammatory bowel disease, and one variant with low hip bone mineral density. These findings further increase the evidence for the marked similarity of genetic risk factors for IBD and AS, consistent with the two diseases having very similar aetiopathogenesis. Disclosure of Interest: None declared